Novel Sigma-2 receptor ligand A011 overcomes MDR in adriamycin-resistant human breast cancer cells by modulating ABCB1 and ABCG2 transporter function - Zeng, Zhanwei; Liao, Shiyi; Zhou, Huan; Liu, Hongyu; Lin, Jiantao; Huang, Yunsheng; Zhou, Chenhui; Xu, Daohua (Frontiers in Pharmacology, 2022)
Multidrug resistance (MDR) is thought to be one of the main reasons for the failure of chemotherapy in cancers. ATP-binding cassette subfamily B member 1 (ABCB1) or P-glycoprotein (P-gp) and ATP-binding cassette subfamily G member 2 (ABCG2) play indispensable roles in cancer cell MDR. Sigma-2 (σ2) receptor is considered to be a cancer biomarker and a potential therapeutic target due to its high expression in various proliferative tumors. Recently, σ2 receptor ligands have been shown to have promising cytotoxic effects against cancer cells and to modulate the activity of P-glycoprotein (ABCB1) in vitro experiments, but their specific effects and mechanisms remain to be elucidated. We found that A011, a σ2 receptor ligand with the structure of 6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline, showed promising cytotoxicity against breast cancer MCF-7 and adriamycin-resistant MCF-7 (MCF-7/ADR), induced apoptosis, and reversed adriamycin (ADR) and paclitaxel resistance in MCF-7/ADR cells. Furthermore, we demonstrated that A011 increased the accumulation of rhodamine 123 and mitoxantrone in MCF-7/ADR cells. A011 significantly decreased the ATPase activity of the ABCB1 and down-regulated ABCG2 protein expression. In addition, A011, administered alone or in combination with ADR, significantly inhibited tumor growth in the MCF-7/ADR tumor-bearing nude mouse model. A011 may be a potential therapeutic agent for the treatment of tumor resistance.